1976
DOI: 10.1097/00005072-197605000-00116
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Astrocytic Differentiation From Embryoid Bodies of an Experimental Mouse Testicular Teratoma

Abstract: Astrocytic differentiation in monolaver cultures of ascitic embrvoid bodies from the experimental teratoma OTT-6050 was studied by conventional light microscopy and by indirect immunofluorescence with antisera to glial fibrillary acidic (GFA) protein, a protein specific for astrocytes. Primitive neuroepithelial cells were identified in 24-hour cultures. Within 72 hours, two cell types diverged. One cell type, with a flattened epithelial morphology in early cultures, demonstrated delicate GFA protein-positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…24 The cultures were examined at 12, 19, and 21 days after having been grown in either Waymouth's medium or DMEM-FI0 medium with or without NGF. Smears from adult mouse cerebellum, fixed in the same manner, were used as positive controis.…”
Section: Immunofluorescence Detection Of Gfa Proteinmentioning
confidence: 99%
“…24 The cultures were examined at 12, 19, and 21 days after having been grown in either Waymouth's medium or DMEM-FI0 medium with or without NGF. Smears from adult mouse cerebellum, fixed in the same manner, were used as positive controis.…”
Section: Immunofluorescence Detection Of Gfa Proteinmentioning
confidence: 99%
“…The correlation between the demonstration of this protein and the presence of 8-10 nm cytoplasmic filaments is not, however, invariable. Increased GFA protein may occur in certain glial cells in the absence of glial filament formation (Bissell, Rubinstein, Rignami & Herman, 1974), and tissue culture of neuroepithelial cell populations of an experimental mouse teratoma has shown that the morphological expression of astrocytic differentiation may be preceded by its biochemical expression (VandenBerg, Ludwin, Herman & Bignami, 1976). Nevertheless, a direct correlation between increased GFA protein production and the formation of glial fibres demonstrable by conventional staining methods is well established (Bignami et al., 1972;Bignami & Dahl, 1974), and the present findings confirm that increased gliofibrillogenesis in uitro is therefore not limited to gliomas of astrocytic origin.…”
Section: Discussionmentioning
confidence: 99%
“…The embryo-derived OTT-6050 teratoma [207] has been extensively analyzed [208][209][210][211][212][213][214][215][216] in regard to the various stages of neuroepithelial differentiation [208][209][210] and constitutes one of the most suitable models for the study of divergent neural differentiation in embryonal CNS tumors. The solid tumors contain a high percentage of neural cells which provide accurate histologic equivalents to the normal stages of neurocytogenesis of the developing avian and mammalian central nervous system and to the embryonal CNS tumors encountered in man [3].…”
Section: Current Experimental Systemsmentioning
confidence: 99%
“…Brain-associated cell surface antigens appear early on neural cells differentiating from the non-neural stem cell populations both in vivo and in vitro [212,213]. Divergent differentiation also occurs early in culture, with the expression of GFA protein [214] and the subsequent presence of biogenic amines as revealed by histochemical fluorescence [209,215].…”
Section: Current Experimental Systemsmentioning
confidence: 99%